8 Can confidence levels of delivering debriefs and feedback be improved in the classroom?. (17th November 2016) - Websdale, Daniel; Purva, M; Major, D; Denning, K
Abstract : Introduction: Debriefing and feedback is a vital part of clinical life and aids learning from experiences and impacts on future clinical outcomes. Confidence is a key factor in delivering feedback. Rosenbaum, M (2004) highlighted that a 'contribution to low confidence is the majority of practicing physicians have reported having no formal training most practitioners learned to give bad news through trial and error'. Poor performance management can lead to breakdown in employer employee relationship. Therefore we designed a course to train clinicians and managers to deliver debriefing and feedback in educational, managerial and clinical setting. Methodology: The one day course used a mixture of lectures and workshops. Theory of debriefing was provided along with practical exercises to review, reflect and appraise their own performance in delivering feedback. Each delegate completed a pre and post course questionnaire with four key questions with a Likert scale of 1 (not confident) to 5 (confident). The course ran twice with a total of 25 people attending over the two dates since September 2015. Results: Confidence levels were recorded against four questions linked to debriefing and feedback. Figures show that mean answer for every question has improved significantly in comparison to the post course. Conclusion: Our course is unique in that 75% of our delegates stated intention was to improve their feedback skills for managerial and clinical settings in contrast to traditional educational settings. It was encouraging to note the improved confidence levels of our attendees. However further work is still needed on more delegates. This can only be done over an extended period of time otherwise courses may become overcrowded and delegates may be less likely to engage in discussion. There is evidence that the techniques they learned throughout the course have gone some way to improving their confidence delivering feedback in the future. Reference: Rosenbaum E Marcy et al . Teaching Medical Students and Residents Skills for Delivering Bad News: A Review of Strategies. Academic Medicine 2004;Volume 79 (No 2):Page 107